Edukasi Manajemen Stres Pada Lansia Dengan Hipertensi di Desa Dukuhwaluh - Sumarni, Tri; Sekar Siwi, Adiratna (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Hypertension remains one of the leading causes of premature death worldwide, including in Indonesia. Data shows that the elderly, especially those in non-productive socioeconomic conditions, are particularly vulnerable to hypertension and its complications. One non-physical factor that exacerbates hypertension is psychological stress, which often goes unnoticed or is not treated properly. The objectives of this activity were (1) to increase knowledge about hypertension, stress, and their impact on health, and (2) to increase knowledge about stress management. This activity was attended by 35 elderly people with hypertension at the Mugi Sehat Posyandu/Posbindu in Dukuhwaluh Village. The activity began with screening for blood pressure, stress levels, and knowledge levels. Then, education about hypertension and stress management was provided. After the education, knowledge levels were measured again. Most of the participants were aged 60-74 years (80%), female (86%), and had a basic education (84%). Regarding blood pressure screening, most participants were in the category of stage 1 hypertension (48%) and moderate stress levels (89%). Before the stress management education, most participants were in the category of adequate knowledge (77%), and after the education, they were in the category of good knowledge (85%). This education was effective in increasing the knowledge of hypertensive patients regarding stress management, so it is hoped that elderly hypertensive patients will be able to manage their stress effectively.